Mathematics
sam4ESG
16

Which equation has no solution? 4(x + 3) + 2x = 6(x + 2) 5 + 2(3 + 2x) = x + 3(x + 1) 5(x + 3) + x = 4(x + 3) + 3 4 + 6(2 + x) = 2(3x + 8)

+1
(1) Answers
Manuel1

Let's solve all equations. First one 4x + 12 + 2x = 6x + 12 (delete both 12, they have the same sign BUT they are in opposite position to the equal) 4x + 2x - 6x = 0 6x - 6x = 0 0x = 0 (it is indeterminated, there are many infinite solutions) Second one 5 + 6 + 4x = x + 3x + 3 4x - x - 3x = 3 - 5 - 6 0x = -8 (impossible) Third one 5(x+3) + x = 4(x+3) + 3 5x + 15 + x = 4x + 12 + 3 5x + x - 4x = 12 + 3 - 15 2x = 0 x = 0 (final answer) Last one 4 + 12 + 6x = 6x + 16 (delete both 6x) 0x = 16 - 4 - 12 0x = 0 (many infinite solutions) ~~~~~~~~~~~~~~~~~~~~~~~~~~~~~ Answer B, the second expression

Add answer